(3GdefJNH ef eSfO YHO Hf MejO GdcTis
(3ChdgG (B:s
(3ef eSfO CHj HcQ GdUOjb QVi Gddg Yfg SeYJ QShd Gddg Udi Gddg Ydjg hSde jbhd (B: (3Ef GdfGS EPG QChG GdXGde ade jCNPhG Ydi jOjg Ch Tc Cf jYege Gddg HGdYbGH s
(3BNQgG (B:s
(3bGd SeYJg jbhd (B: (3ef QeiHSge ai SHjd Gddg cG Pdc YOd YJb QbHI s
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdMOjK h GdeUWdMs